Retrospective analysis of blunt force trauma associated with fatal road traffic accidents in Cape Town (South Africa) over a two-year period - Majero, T A Tiffany (Division of Forensic Medicine and Toxicology, 2019)
Road transportation systems are a global developmental achievement. However, with them comes increased morbidity and mortality rates in the form of road traffic accidents. In South Africa, there is a need to characterize road traffic accidents and the injuries associated with them, to determine the preventative mechanisms required to reduce their morbidity and mortality rates. A brief review of fatal road traffic accidents from a global perspective is presented, highlighting the current literature surrounding the prevalence, demographics and blunt force trauma injuries associated with road traffic accidents in South Africa. There is limited research regarding the prevalence and characteristics of road traffic accidents. The objective of this study was to determine the prevalence of fatal road traffic accidents, necessitating the need for research, particularly at the regional level. A retrospective analysis was therefore conducted of all fatal road traffic accident related deaths autopsied at Salt River Mortuary (which services the West Metropole region of Cape Town, South Africa) from January 1st , 2013 to December 31st , 2014. The mean prevalence of road traffic accidents for the reviewed period was 15.9 / 100 000 population. The majority of road traffic accident victims were males who fell in the age group of 30 – 49 years. Over the two-year period, the majority of road traffic accident victims were pedestrians with elevated blood alcohol concentration levels. The head and facial regions of victims commonly exhibited external injuries, while the majority of fractures and organ injury were seen in the head and chest regions. There are limited studies which have investigated the blunt force trauma injuries associated with road traffic accidents in South Africa, and there is a need for further research. Interventions are of paramount importance to decrease fatal road traffic accidents, particularly amongst pedestrians as a road user. This study presents recent data on road traffic accidents for the West Metropole region of Cape Town (South Africa).